The Role Of Islamic Educational Institutions in The Formation of Malay Cultural Identity in Indonesia and Brunei Darussalam - Nurani, Leni (Proceedings: International Seminar On Educational Studies, 2025)
This study examines the role of Islamic educational institutions in shaping the Malay cultural identity in Indonesia and Brunei Darussalam as an integral part of the Malay-Islamic Civilization (Tamadun Islam Nusantara). The study is motivated by the academic gap in understanding how Islamic education functions not only as a medium for transmitting religious knowledge but also as an agent for preserving Malay-Islamic cultural values. The objective of this research is to comparatively analyze the models of Islamic education in Indonesia and Brunei and their implications for the development of the Malay-Islamic civilization in the Southeast Asian region. The study employs a qualitative approach with a literature review design, drawing on national and international scholarly sources. The analysis identifies the similarities and differences in the educational systems of both countries based on historical, ideological, and sociocultural dimensions. The findings reveal that Indonesia represents an inclusive, adaptive, and pluralistic model of Islamic education, whereas Brunei implements an educational system integrated within the philosophy of Melayu Islam Beraja, emphasizing value uniformity and social loyalty. These distinctions illustrate two complementary paradigms of civilization that sustain the continuity of Malay-Islamic identity. The study concludes that Islamic education in both nations plays a strategic role in strengthening the cultural and spiritual heritage of the Malay world while serving as a fundamental pillar for the development of an Islamic civilization rooted in local values with a global outlook.